Parasitos de peixes como bioindicadores de impactos ambientais e análise da qualidade química da água nos rios jacaré-pepira e jacaré-guaçu, bacia hidrográfica do Tietê- Jacaré, estado de São Paulo, Brasil - Jacovani, Kerolaine Suelllen de Melo (2019)
In recent decades, aquatic ecosystems have been significantly altered due to multiple environmental impacts from anthropic activities. When environmental monitoring is necessary to identify potentially shocking modifications, a broad environmental analysis such as chemical analysis of the water, application of habitat assessments and accurate analyzes of certain elements As, Cr, Cd e Pb considered to be potentially toxic at high or low concentrations is necessary. In order to carry out this evaluation, this study applied a rapid analysis of habitats in the Jacaré-Guaçu and Jacaré-Pepira rivers of the Tietê-Jacaré basin, together with the chemical analysis of the water and to verify the possible impact on the aquatic communities. Quantification of trace elements considered as toxic As, Cr, Cd and Pb in parasites, hosts and water, verifying the potential accumulation of these elements in the parasites. As a result an alert for eutrophication of the site, strong antropic influence in both rivers and a positive result for the capacity of accumulation of trace elements As, Cr, Cd e Pb in the parasites being its concentration higher than the host and, the host greater than the concentrations found in the water which is in accordance with the legislation, indicating that the concentration even low in the environment leads to accumulation due to the time of exposure to the environment.